Extremely enrichment of 7Li in highly weathered saprolites developed on granite from Huizhou, southern China. (February 2021) - Zhang, Jun-Wen; Zhao, Zhi-Qi; Li, Xiao-Dong; Yan, Ya-Ni; Lang, Yun-Chao; Ding, Hu; Cui, Li-Feng; Meng, Jun-Lun; Liu, Cong-Qiang
Abstract: Lithium isotope is potentially useful tracer of continental weathering. However, the factors affecting Li isotope composition in highly weathered saprolites are still largely unclear. In the present study, Li and Nd isotope compositions in saprolites developed on granite from Huizhou, southern China, were analyzed and Li isotope composition in quartz samples separated from the saprolites was determined. The Nd isotope composition of saprolites (εNd  = −6.1 ± 0.4, 1σ) was almost identical to that of parent granite (εNd  = −5.7), suggesting the eolian deposition in this profile is negligible. The δ 7 Li value in saprolites varied greatly from −7.7‰ to +14.0‰. Below a depth of 3 m, almost all saprolites were isotopically lighter than the parent granite (+1.0‰). However, above 3 m, δ 7 Li values were higher in saprolites (+2.2‰ to +14.0‰, average + 7.6‰) than in the parent granite and showed a significant increasing trend toward the surface. Moreover, the δ 7 Li value showed a negative correlation with the CIA value below 3 m, but a positive correlation above 3 m. Compared with the parent granite, quartz separates had a higher Li concentration (1.1–28.9 mg/kg, average 9.5 mg/kg) and δ 7 Li value (+12.1‰ to +13.9‰). As weathering progressed, the formation of secondary minerals (such as kaolinite) led to the incorporation of lighter 6 Li, which may have contributed significantly to the low δ 7 Li value in saprolites below 3 m. However, this mechanism could not explain the relative enrichment of heavy 7 Li in the upper layer saprolites. The relative enrichment of quartz may contribute significantly to the increase of δ 7 Li in saprolites. The direct evidence was that Li was abundant and distinctly isotopically heavier in quartz separates. Moreover, quartz content correlated positively with Li concentration (R 2  = 0.90, p  < 0.01) and δ 7 Li value (R 2  = 0.90, p  < 0.01) in the upper layer saprolites. The results showed that a 10% increase in Li due to quartz enrichment (δ 7 Li = ~+13‰) resulted in a +1.3‰ increase in δ 7 Li in the saprolites. Our results highlight that relative enrichment of quartz may result in isotopically heavier Li in highly weathered saprolites developed on granite, which may help to explain the higher δ 7 Li values detected near the surface layer of weathering profiles. Highlights: Enrichment of 7 Li in highly weathered saprolites developed on granite was observed. Lithium was relatively abundant and isotopically heavy in quartz. Quartz enrichment was the major cause of high δ 7 Li in saprolites.